Co-generation and maintenance of ‘dialogic space’ by means of verbal-gestural involvement, with some pedagogical implications - Puppel, Joanna; Puppel, Stanisław (Scripta Neophilologica Posnaniensia, 2019)
We emphasize that ‘dialogic space’ is a precondition to the presence and maintenance of collective culture whose most conspicuous dimension is dialogic culture. We assume that dialogic culture constitutes the fullest dimension of humanity, and we highlight its role in a number of assumptions (1-8). Next, dialogic culture in terms of its properties is briefly discussed. We further assume that dialogic space in its verbal-non-verbal tanglements is of central significance in foreign language pedagogy and as such it should be present in foreign teaching/learning programs in order to help promote the positively-charged dialogue-oriented society of practice and at the same time exclude the proliferation of negatively-charged communications.